Teacher’s Perceptions of Islamic Science Learning Using a Scientific Approach Assisted by “Selawat Science” - Yuniar Fahmi Lathif; Sarwi Sarwi; Putut Marwoto; Endang Susilaningsih (International Conference on Science, Education, and Technology, 2021)
This study aims to describe the teacher's perception of learning science with a scientific approach assisted by "selawat science" in learning the solar system for first grade junior high school students. The research subjects consisted of 15 junior high school teachers in Kudus Regency. Quantitative survey method was used to obtain teacher perception data. The results of the study indicate that the scientific approach assisted by scientific research is in accordance with the characteristics of Islamic boarding schools students, develops students' multiple skills, increases learning motivation so that students are more active during the learning process and adds insight to teachers in integrating science and religion. Obstacles felt by teachers include inadequate science laboratory facilities and some teachers have difficulty integrating science and selawat because they do not have a pesantren education background.